2013
DOI: 10.3390/e15104285
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metrics and a Complexity Scale for the Topology of Assembly Supply Chains

Abstract: Abstract:In this paper, we present a methodological framework for conceptual modeling of assembly supply chain (ASC) networks. Models of such ASC networks are divided into classes on the basis of the numbers of initial suppliers. We provide a brief overview of select literature on the topic of structural complexity in assembly systems. Subsequently, the so called Vertex degree index for measuring a structural complexity of ASC networks is applied. This measure, which is based on the Shannon entropy, is well su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The different interactions of networks has been investigated by Demetrius and Manke [36], who demonstrated four classic structures: regular, random, scale-free, and star networks with the same number of nodes n and links e. The average shortest path length L of different networks were shown as L regular > L random > L scale− f ree > L star , while the network entropy were reversely shown as H star > H scale− f ree > H random > H regular . Therefore shortening L in SN is considered as a way to increase SN efficiency [10,12,13,36,41]. Furthermore, we found that an SN with high network entropy represented the high complexity of SN interdependence, which led to SN efficiency.…”
Section: Discussion Of Network Complexitymentioning
confidence: 86%
See 4 more Smart Citations
“…The different interactions of networks has been investigated by Demetrius and Manke [36], who demonstrated four classic structures: regular, random, scale-free, and star networks with the same number of nodes n and links e. The average shortest path length L of different networks were shown as L regular > L random > L scale− f ree > L star , while the network entropy were reversely shown as H star > H scale− f ree > H random > H regular . Therefore shortening L in SN is considered as a way to increase SN efficiency [10,12,13,36,41]. Furthermore, we found that an SN with high network entropy represented the high complexity of SN interdependence, which led to SN efficiency.…”
Section: Discussion Of Network Complexitymentioning
confidence: 86%
“…It is well known that a higher complex network makes it more difficult to understand relational interactions and topological characteristics, so only a small change can cause a massive reaction [41]. On the other hand, as network is a nonlinear system, even given the same number of nodes and edges, networks can represent completely different structures such as regular, random, scale-free network and star networks [36].…”
Section: Discussion Of Network Complexitymentioning
confidence: 99%
See 3 more Smart Citations